Efektifitas Pengawetan Batang Kelapa Sawit (Elaeis guinensis Jacq.) Terhadap Serangan Rayap Tanah (Coptotermes curvignathus Holmgren) Menggunakan Campuran Boraks dan Asam Borat - Harsono, Dwi (Jurnal Riset Industri Hasil Hutan, 2016)
Oil palm trunk has a high moisture content about 60%-300% depended on the height and age of the tree and it was presumed to have low quality and prone to decay by organisms. It is necessary to improve the trunk quality using preservatives. The purpose of this study is to calculate the value of the penetration and retention, to test the durability of oil palm trunk from the attack of termites after treated with a mixed preservative of borax and boric acid. This study used the free of defects trunk obtained from PT. Buana Karya Bhakti in Tanah Bumbu, South Kalimantan, planted in 1998 (Â±18 years old). The research used two factors: A (the preservative concentration variations) = a1 (5%); a2 (10%); a3 (15%); and B (soaking time variation) = b1 (1 day); b2 (3 days); b3 (5 days). The results showed that the trunk water content was 14.62%, the density was 0.25 g/cm3, the radial shrinkage was 1.48% and the tangential shrinkage was 2.17%. The average of boron penetration was 50 mm. The highest retention was got from the treatment of boron concentration 15% in 2 days for 54.71 kg/m3, while the lowest retention was from 5% boron in 1-day treatment for 13.7 kg/m3. The weight loss ranged from 19.30%-41.32%, and the average of termites attack degree ranged between 40% and 70% (categorized as moderate), while the control was decayed completely by termites in both experiments. The mortality rate in all treatments was 100%, while the control ranged from 7%-10.5%.Keywords: oil palm trunk, preservation, boron, termites